Tradisi Melukat Menurunkan Kecemasan Ibu Hamil Menjelang Persalinan di Desa Bungkulan - Bukian, Putu Agus Windu Yasa; Sujana, I Wayan; Jayendra, Putu Sabda (JIA (Jurnal Ilmu Agama), 2024)
Third trimester pregnant women are very vulnerable to experiencing anxiety, this is because pregnant women are not yet mentally, spiritually and physically ready to face the birthing process. Pregnant women who are anxious will affect the mother's readiness for childbirth and can even affect the condition of the fetus in the womb if the mother's anxiety continues. The aim of this study was to analyze the differences in anxiety of pregnant women in the third trimester before and after the melukat tradition was carried out. This research method uses quantitative with a onegroup preposttest design approach. The population is all pregnant women in Bungkulan Village with a minimum sample size of 78 pregnant women. The sampling technique was purposive sampling and the research instrument used an anxiety questionnaire. Furthermore, the analysis used was univariate and bivariate using Wilcoxon because the data was not normally distributed. The results of this study found that the difference in the average anxiety felt by mothers before and after being injured was with a Z value of 4.65. These results are also statistically significant in that melukat is an activity that can reduce maternal anxiety before the third trimester birth process. The conclusion is that there are differences in anxiety before and after wounding pregnant women.